Application of Project Management in e-procurement. Issue 2 (14th January 2008) - Foulds, L.R.; West, M.; Jin, Yi
Procurement is a key process in the supply chain and, with the advent of internet, procurement processes have had to be redesigned and reorganised. This has led businesses around the globe to embrace e-procurement in order to enhance the management of their supply chains and the facilitation of their procurement processes. Internet-based procurement technologies are fundamentally changing the way purchasers buy goods. However, in spite of the promise that e-procurement holds, because they have found the implementation process to be more complex, expensive, and time consuming than originally expected, many firms have not received the hoped-for benefits from e-procurement investment. Over the last 30 years, Project Management (PM) has been recognised as an efficient tool for managing novel and complex activities. PM is becoming ever more important in ensuring organisational success, and is now widely seen as a critical enabler for the attainment of strategic goals. This paper explores the possibility of applying PM principles in order to enhance supply-chain and e-procurement management. The main findings indicate that most managers are able to see the potential benefits of PM technology to their e-procurement processes within supply chain management. An important conclusion of the research is that, supply-chain organisations that intend to apply PM principles to e-procurement management need to develop a PM-oriented culture, based on shared organisational values.